2018
DOI: 10.1002/jper.17-0341
|View full text |Cite
|
Sign up to set email alerts
|

Activation of autophagy in periodontal ligament mesenchymal stem cells promotes angiogenesis in periodontitis

Abstract: Autophagy modulates angiogenesis-promoting ability of PDLSCs, which could be increased by an inflammatory environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 35 publications
0
54
0
3
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have been widely reported to be associated with angiogenesis, including dental stem cells [4,8,9]. Periodontal ligament stem cells (PDLSCs) are a class of odontogenic MSCs residing in periodontal ligament with functions of self-renewal, multi-directional differentiation potential and cellular regulation [10].…”
Section: Ivyspringmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesenchymal stem cells (MSCs) have been widely reported to be associated with angiogenesis, including dental stem cells [4,8,9]. Periodontal ligament stem cells (PDLSCs) are a class of odontogenic MSCs residing in periodontal ligament with functions of self-renewal, multi-directional differentiation potential and cellular regulation [10].…”
Section: Ivyspringmentioning
confidence: 99%
“…Periodontal ligament stem cells (PDLSCs) are a class of odontogenic MSCs residing in periodontal ligament with functions of self-renewal, multi-directional differentiation potential and cellular regulation [10]. Recent study reported that PDLSCs had an ability of angiogenic promotion [4,9], whereas the underlying mechanism of PDLSCs on angiogenesis under inflammatory micro-environment needed to be uncovered.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, angiogenesis was inhibited when the autophagy was suppressed via silencing Beclin‐1, an important factor in autophagy flux. These findings suggested that inflammation‐related autophagy in PDLSCs might regulate the angiogenesis ability in periodontium (Wei, An, An, Fei, & Wang, ).…”
Section: Autophagy and Periodontal Inflammationmentioning
confidence: 98%
“…Autophagy is a biological process by which autophagosomes are formed and then fused with lysosomes to degrade autophagic contents by lysosomal protease. Autophagy can promote angiogenesis under inflammatory stimulation, hypoxia or high-glucose microenvironments [139,140]. Transcription factor EB (TFEB) is a master regulator of autophagy and lysosomal biogenesis.…”
Section: Inducing Autophagymentioning
confidence: 99%